The Study of Job Satisfaction : Exploring Work-Life Balance, Job Stress, and Burnout - Nurjihan Erlinda; Dewi Khrisna Sawitri (Dinasti Publisher, 2025)
The present research examines the influence of work life balance and job stress on job satisfaction, with burnout as a mediating variable among employees of the Operations Directorate at public service company in Surabaya. Job satisfaction is essential as it affects employee motivation and productivity. The research uses a quantitative approach with 70 respondents selected using Slovin’s formula and analyzed through the SEM-PLS method. The results show that maintaining work-life balance contributes positively and meaningfully to job satisfaction, while job stress has a negative and significant effect. Additionally, burnout mediates the effect of both work-life balance and job stress on job satisfaction, indicating that less burnout is related to higher levels of job satisfaction.